2021
DOI: 10.4049/jimmunol.2000663
|View full text |Cite
|
Sign up to set email alerts
|

Gut Commensal Segmented Filamentous Bacteria Fine-Tune T Follicular Regulatory Cells to Modify the Severity of Systemic Autoimmune Arthritis

Abstract: Autoantibodies play a major pathogenic role in rheumatoid arthritis. T follicular helper (Tfh) cells promote germinal center B cell and Ab responses. Excessive Tfh cell responses lead to autoimmunity, and therefore, counterregulation is crucial. T follicular regulatory (Tfr) cells, mainly differentiated from T regulatory cells, can negatively regulate Tfh and germinal center B cells. Dysbiosis is involved in rheumatoid arthritis's pathogenesis. We previously demonstrated that the gut microbiota, segmented fila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…This is compatible with the decreased Th17 cell population and increased Tfh cell population seen in the K/BxN model occurring during ageing, which also depends on the gut microbiota. Very recently, gut microbiota has been shown to influence systemic Tfr cells, impacting systemic autoimmunity in the present animal model of autoimmune arthritis (59). This means the implication of the local microbiota and nervous circuits in the regulation of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 74%
“…This is compatible with the decreased Th17 cell population and increased Tfh cell population seen in the K/BxN model occurring during ageing, which also depends on the gut microbiota. Very recently, gut microbiota has been shown to influence systemic Tfr cells, impacting systemic autoimmunity in the present animal model of autoimmune arthritis (59). This means the implication of the local microbiota and nervous circuits in the regulation of autoimmune diseases.…”
Section: Discussionmentioning
confidence: 74%
“…Some Treg cells are also found in B-cell follicles and were identified as T follicular regulatory (Tfr) cells. These cells can migrate into the GC, thereby inhibiting B-cell maturation and antibody production [ 163 ] SFB, which induces Tfh cells to promote autoimmune arthritis, has also exhibited the potential to influence systemic Tfr cells [ 164 ]. In addition, butyrate is an environmental cue that can induce the differentiation of Tfr cells, which can also ameliorate autoimmune arthritis [ 165 ].…”
Section: The Interplay Between the Immune System And The Gut Microbiotamentioning
confidence: 99%
“…Other notable bacterial shifts in the gut microbiota for RA patients include a bloom in Proteobacteria, Clostridium cluster XlVa, and Ruminococcus, which were correlated with less CD4 + T cells and Treg cells [348]. Using the K/BxN autoimmune arthritis model, it was found that SFB-mediated cytotoxic T lymphocyte antigen-4 (CTLA-4) reduction caused autoreactive T follicular helper cells [349,350]. The accumulation of T follicular helper cells and Th17 cells in arthritis appears to be age-dependent [351], which helps to explain why RA is found mostly in the older population.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%